Bioactive Compounds of Rosa canina L. and Their Effect on Tumor Necrosis Factor-α and Interleukin-1β Activity in Diabetes-Induced Rats - YALÇINKAYA, İlayda Sezin; AKTAN, Onur; AÇIK, Leyla; ERKMEN, Gülnihal KULAKSIZ; VURAL, NILUFER; KAYMAK, Sibel; ATEŞ, Yiğit Can (Sciences of Pharmacy, 2024)
The ethnopharmacological significance of Rosa canina, or dog rose, transcends diverse cultures, with traditional applications in treating various diseases. This study investigates the potential pharmacological application of Rosa canina for diabetes treatment, aiming to assess its antidiabetic properties through in vitro, in vivo, and in silico analyses targeting pro-cytokines. Biochemical profiling utilizing HPLC, and phenolic content analyses were conducted to reveal the antioxidant properties of Rosa canina. In diabetic rats, root extracts influenced the expression of TNF-α and IL-1β, with an exploration of DNA-binding and protective activities. DPPH scavenging and iron chelating activities were measured, identifying significant IC50 values. The chromatographic analysis identified various compounds, with Kaempferol 3-O-glucoside and Rutin exhibiting high inhibitory activity against TNF-alpha. In silico analyses highlighted inhibitory activities by molecular docking against TNF-α and IL-1β (PDB IDs 2AZ5 and 9ILB, respectively) and their drug potential based on ADMET properties. The obtained results have demonstrated a significant decrease in blood glucose levels in mice through the reduction of TNF-α and IL-1β mediated diabetic processes, facilitated by the Rosa canina extract. In conclusion, this study exploring the effects of Rosa canina extracts on diabetic rats have provided valuable insights into its potential therapeutic benefits. The observed reductions in blood glucose levels, improvements in lipid profiles, and modulation of antioxidant activity highlight its promising role in managing diabetes-related complications. Further research is warranted to elucidate the underlying mechanisms and optimize the dosage regimens for harnessing the full therapeutic potential of Rosa canina extracts in diabetes management.